Web-Based Inventory Information System For Monitoring Stock, At PT. Sarah Ayu Semarang Branch - Wijaya Heti Susanti; Danang Danang; Neilin Nikhlis (Lembaga Pengembangan Kinerja Dosen, 2023)
Sarah Ayu Semarang Branch is a company that operates in the rental and sales of children's toys. To fulfill the wishes of several outlets in Semarang, the company has a storage warehouse, but the documentation currently used is still simple by recording stock of goods by looking directly at the existing goods, calculating using a calculator and recording it in a book as a report to the management. In this way, differences often occur between real (real) goods stock with monthly goods recording from the head office. This research discusses a web -based inventory information system for monitoring stock at PT. Sarah Ayu Semarang Branch. By designing an application that is capable of processing, documenting, calculating order transactions, and storing inventory in the warehouse. By having minimum stock and maximum stock, the company can find out the amount of inventory that is running out and over stock, while the company can easily find out the final stock amount of goods in the warehouse. Web- Based Inventory Information System is also really needed in companies to help warehouse divisions, administration and leaders in making decisions. To build the system using the PHP programming language MYSQL database . With this inventory information system, it is hoped that the company will be able to carry out planning in making decisions and monitoring inventory properly, and be able to carry out stock control functions including items that are running out or over stock , while also being able to produce reports that are accurate, fast and precise.